2009
DOI: 10.1002/ejoc.200901002
|View full text |Cite
|
Sign up to set email alerts
|

Configurational Isomers of a Stilbene‐Linked Bis(porphyrin) Tweezer: Synthesis and Fullerene‐Binding Studies

Abstract: A new stilbene-tethered bis(porphyrin) tweezer 5 has been synthesized through a Sonogashira cross-coupling reaction. The tweezer exists as two configurational isomers [(Z) + (E)], which have distinct cavity sizes. Fullerene-binding studies show that the (Z) isomer of the tweezer has a significantly

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 28 publications
(4 reference statements)
0
12
0
Order By: Relevance
“…Similar copper‐free cross‐coupling reaction conditions have already been used for the synthesis of porphyrin dimers and trimers by Achelle et al in 2011 and are reported to be well suited to porphyrin systems 2327. All the coupling reactions presented herein used the same monomeric ethynylporphyrin building block 5 (Scheme ), which can be synthesized from the dipyrromethane compound 6 , TMS‐propynal ( 7 ), and pentafluorobenzaldehyde ( 8 ) following the general procedure reported for the synthesis of unsymmetrical porphyrins by Fathalla and Jayawickramarajah 28. This statistical reaction yields three different porphyrins, namely compound 5 , meso ‐tetrakis(pentafluorophenyl)porphyrin ( 5a ), and the diethynyl derivative 5b (Scheme ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Similar copper‐free cross‐coupling reaction conditions have already been used for the synthesis of porphyrin dimers and trimers by Achelle et al in 2011 and are reported to be well suited to porphyrin systems 2327. All the coupling reactions presented herein used the same monomeric ethynylporphyrin building block 5 (Scheme ), which can be synthesized from the dipyrromethane compound 6 , TMS‐propynal ( 7 ), and pentafluorobenzaldehyde ( 8 ) following the general procedure reported for the synthesis of unsymmetrical porphyrins by Fathalla and Jayawickramarajah 28. This statistical reaction yields three different porphyrins, namely compound 5 , meso ‐tetrakis(pentafluorophenyl)porphyrin ( 5a ), and the diethynyl derivative 5b (Scheme ).…”
Section: Resultsmentioning
confidence: 99%
“…Subsequent oxidization with 2,3‐dichloro‐5,6‐dicyano‐1,4‐benzoquinone (DDQ) provided the desired porphyrin derivative. The reaction conditions reported by Fathalla and Jayawickramarajah in 2009 for non‐fluorinated porphyrins were systematically varied (Table 1), seeking to optimize the conditions for the fluorinated starting materials 28,33. Longer reaction times increased the yield, and replacing DDQ by p ‐chloranil reduced the isolated yield of the reaction.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As a different family of efficient bidentate receptors are regularly reported, bis(metalloporphyrin) derivatives, which utilize metalloporphyrins for their high binding abilities and high absorbance in the visible region. [5][6][7][8][9][10][11][12][13][14][15][16] Thus, it is expected that metalloporphyrin-Tröger's base conjugates would be effective enantioselective receptors, since they join the best properties from both structural motives.…”
Section: Introductionmentioning
confidence: 99%